Approaches to teaching and teacher education : ISATT 40th anniversary yearbook - Craig, Cheryl J.; Mena, Juanjo; Kane, Ruth G. (Advances in research on teaching ;, 2023)
This volume contains an Open Access Chapter Research on teacher education and classroom teaching has evolved significantly in recent decades, with more research taking an international or intersectional lens. The International Study Association on Teachers and Teaching (ISATT) has moved with the field, beginning as a predominantly white European and North American organization in 1983, it now has active membership from more than 60 countries across the globe. The ISATT 40th Anniversary Yearbook, presented over three volumes, reflects this growth through celebrating the contributions of ISATT members over time and offering current scholarly research to inform current and future teacher education and teaching. Bringing together top research from the Finnish Educational Research Association (FERA) and Taylor & Francis published over the past 10 years, plus cutting-edge new chapters, Approaches to Teaching and Teacher Education explores established and innovative approaches to teaching and teacher support. The chapters explore teacher development, identity, morals, ethics and politics and teaching and teacher education with vulnerable and marginalized populations. All three volumes that make up the ISATT 40th Anniversary Yearbook offer invaluable insights for teacher educators and educational researchers the world over, offering international perspectives from North America, Europe, South America, Asia, Africa, and Australasia.